2019
DOI: 10.1111/coa.13381
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of sound localisation in single‐sided deaf adults fitted with a BAHA device

Abstract: Objective To perform a long‐term evaluation of the localisation capabilities in the horizontal plane of single‐sided deaf patients fitted with a BAHA device. Design Single‐centre retrospective study. Participants Twenty‐one adults with single‐sided deafness (SSD) with normal hearing in the contralateral ear (pure tone average <20 dB, SDS > 90%) rehabilitated with a Cochlear BAHA device from 2003 to 2012 on the deaf side over a median follow‐up of 8 years. Outcome measures The task used in this paper is a sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…have demonstrated that localisation abilities in the horizontal planes are effectively enhanced in patients with single-sided deafness using BAHA devices during an average follow up of eight years. 14 Further, Bonne et al . suggested that the improvement may be related to the influence of device training and learning, the design of testing, the employment of distorted temporal cues and the reconstruction of the body map.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…have demonstrated that localisation abilities in the horizontal planes are effectively enhanced in patients with single-sided deafness using BAHA devices during an average follow up of eight years. 14 Further, Bonne et al . suggested that the improvement may be related to the influence of device training and learning, the design of testing, the employment of distorted temporal cues and the reconstruction of the body map.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another method used to improve hearing for patients with single-sided deafness is the bone-conduction hearing aid devices, which include bone-anchored hearing aids (BAHA; Cochlear ® ), the Baha ® Attract system (Cochlear ® ) and the Sophono ® , which make the amplified sound stimulate the contralateral normal-hearing cochlea via transcranial direct bone-conduction. [12][13][14][15][16] Data have shown that bone-conduction hearing aid devices can provide important amplification in hearing performance for single-sided deafness, improve patients' speech discrimination abilities in noisy environments and improve their QoL. While the bone-conduction hearing aid has led to certain benefits in hearing gain and patient satisfaction, it also results in some complications because of the percutaneous coupling that is required for fitting, including skin infection, soft tissue overgrowth of the abutment, failure to osseointegrate and loss of the titanium implant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCHD is an effective hearing solution for people with a conductive hearing loss (CHL) or mixed hearing loss (MHL), as they bypass any limitations on sound transmission associated with pathologies or anomalies of the outer or middle ear (den Besten et al 2019;Dimitriadis et al 2016;Iseri et al 2015). These devices can also help patients who suffer from single-sided deafness by transmitting sound received on the deaf side directly to the hearing cochlea (den Besten et al 2019;Bonne et al 2019;Flynn et al 2010). BCHD bypasses the conductive part of the hearing loss and, as such, inherently closes the air-bone gap (ABG).…”
Section: Introductionmentioning
confidence: 99%